Population III microquasars - Romero, Gustavo Esteban (2018)
We present the first results obtained in the elaboration of a complete model of a microquasar where the donor star is from Population III. These stars do not produce stellar winds so we consider that the mass loss is due exclusively to matter overflowing the Roche lobe towards the compact object, a maximally rotating black hole. The rate of accretion is extremely super-Eddington, with an intense mass loss from the system in the form of winds and jets. We calculate the relativistic particle content of the jet and the corresponding spectral energy distribution (SED) considering a lepto-hadronic model. Prospects for the cosmological implications of these objects are briefly discussed.